2021
DOI: 10.1088/1748-0221/16/10/c10006
|View full text |Cite
|
Sign up to set email alerts
|

Comparing different bulk radiation damage models in TCAD simulations of small-pitch 3D Si sensors

Abstract: Small-pitch, thin 3D Si sensors have been developed for the ATLAS and CMS experiment upgrades at the High Luminosity LHC. The pixel sizes are 50 × 50 µm2 with 1 readout column, and 25 × 100 µm2 with 1 or 2 readout columns (1E and 2E). Owing to the small inter-electrode distance, ranging from ∼28 µm to ∼51 µm in the considered layouts, these devices are expected to be extremely radiation hard. TCAD simulations by Synopsys Sentaurus, incorporating advanced radiation damage models, have been used for the design/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The Perugia model predicts the magnitude of the leakage current and of the breakdown voltage, but the shape of the I-V curve is different from the measured ones. In particular, a plateau in the I-V curve is soon reached due to the fact that the model underestimates the full depletion voltage, as was also found in a previous study [23]. Moreover, an abrupt increase in the current is observed at breakdown, whereas the measured curves exhibit a smooth rise.…”
Section: Combined Effectssupporting
confidence: 78%
“…The Perugia model predicts the magnitude of the leakage current and of the breakdown voltage, but the shape of the I-V curve is different from the measured ones. In particular, a plateau in the I-V curve is soon reached due to the fact that the model underestimates the full depletion voltage, as was also found in a previous study [23]. Moreover, an abrupt increase in the current is observed at breakdown, whereas the measured curves exhibit a smooth rise.…”
Section: Combined Effectssupporting
confidence: 78%
“…After irradiation up to 2 × 10 16 n eq /cm 2 , the proposed design is comparable to the existing one in terms of signal efficiency and superior to 3D pixels with columnar electrodes of similar inter-electrode distance [21]. Moreover, the electric field non-uniformity also impacts on the signal efficiency at high voltage: in particular, charge multiplication effects are position dependent and actually stronger in the boundary region between adjacent pixels.…”
Section: Discussionmentioning
confidence: 79%
“…This model was initially validated for a temperature range from −38.1 °C to −31.1 (here we use −37.9 °C) up to a radiation fluence of 8 × 10 15 n eq /cm 2 . However, we have previously demonstrated that simulation results in terms of signal efficiency (i.e., the ratio of the charge signal amplitude after irradiation and before irradiation) are accurate up to 2 × 10 16 n eq /cm 2 [21], so the model is here used up to this higher limit.…”
Section: Simulation Approachmentioning
confidence: 99%
“…The energy resolution of an SSBD device is closely related to charge collection efficiency and leakage current. To reduce the leakage current, many works to have attempted to modify the metal-semiconductor interface and enhance the Schottky barrier height [5][6][7]. For excellent detection efficiency, the detectors should operate at a high electric field or reduce the thickness of substrate.…”
Section: Introductionmentioning
confidence: 99%